2023
DOI: 10.3389/fpsyt.2023.1161488
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of estradiol and progesterone on woman's disgust processing

Abstract: BackgroundOvarian hormones play a critical role in emotion processing, which may be a major reason for the high rates of major depressive disorders in women. However, the exact roles of estradiol and progesterone in emotional processing remain unclear. To this end, we performed behavioral and rs-fMRI studies on the effects ovarian hormones on disgust emotion.MethodsIn Experiment 1, 95 Chinese female undergraduates completed the single category implicit association test (SC-IAT) and explicit measures of disgust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…They are known to shift the immune response towards Th2 dominance [66]. Moreover, some studies have observed higher levels of disgust sensitivity during the luteal phase of the menstrual cycle, when estrogen levels are elevated, compared to the menstrual phase [20,23], aligning with our findings. Conversely, our results are not in line with two studies that found no association between salivary estradiol levels and disgust sensitivity measured via TDDS [18,29].…”
Section: Estrogens and Disgust Sensitivitysupporting
confidence: 91%
See 1 more Smart Citation
“…They are known to shift the immune response towards Th2 dominance [66]. Moreover, some studies have observed higher levels of disgust sensitivity during the luteal phase of the menstrual cycle, when estrogen levels are elevated, compared to the menstrual phase [20,23], aligning with our findings. Conversely, our results are not in line with two studies that found no association between salivary estradiol levels and disgust sensitivity measured via TDDS [18,29].…”
Section: Estrogens and Disgust Sensitivitysupporting
confidence: 91%
“…A cross-sectional study also found elevated disgust sensitivity during the luteal phase in a subsample of women who recently had an infection [22]. In a recent study, women in the luteal phase displayed a more negative attitude and higher sensitivity to disgust-related phrases compared to women tested during the follicular phase or menstruation [23].…”
Section: Introductionmentioning
confidence: 87%
“…Similarly, people with menstrual cycles experience weaker feelings of disgust during high estrogen and low progesterone periods, such as around ovulation, which is proposed to be adaptive for mating behavior. 44 …”
Section: Discussionmentioning
confidence: 99%